Association of Hypomorphic P2X7 Receptor Genotype With Age - Sanz, Juana Maria; Falzoni, Simonetta; Morieri, Mario Luca; Passaro, Angelina; Zuliani, Giovanni; Di Virgilio, Francesco (Frontiers in Molecular Neuroscience, 2020)
One of the main risk factors for brain diseases is aging. Recent studies have shown that aging is a progressive degenerative process associated with chronic low-level inflammation. The ATP-gated P2X7 receptor (P2X7R) plays an important role in inflammation and has been associated with different brain (e.g. Alzheimer’s and Parkinson’s) or other age-related (osteoporosis, arthritis, cancer) diseases. Several single nucleotide polymorphisms (SNPs) in the P2RX7 gene have been identified, including the loss-of-function 1513A>C and 1405A>G SNPs, and the gain-of-function 489C>T and 1068G>A SNPs. We carried out a literature analysis to verify an association between P2RX7 SNPs frequency and age. In 34 world-wide eligible studies (11.858 subjects) no correlation between 1513CC genotype frequency and age emerged. On the contrary, analysis of European Caucasian cohorts (7.241 subjects) showed a significant increase of 1513CC frequency with age (P=0.027). In agreement with these findings, analysis of two public available datasets including USA Caucasian cohorts unveiled an increased frequency of 1513CC and 489CC genotypes with age (P=0.0055 and P=0.0052, respectively). Thus, hypomorphic P2RX7 genotypes may be positively selected with age in European and North-American Caucasian population. We hypothesize that Caucasian individuals bearing an anti-inflammatory P2X7R phenotype living in high-income countries may have a longer life expectancy.